A Finite Element (FE) Simulation of Naked Solid Steel Beam at Elevated Temperature - Ahmad Zakwan, Fariz Aswan; Krishnamoorthy, Renga Rao; Ibrahim, Azmi; Ismail, Ruqayyah (International Journal of Integrated Engineering, 2019)
This paper presents the numerical analysis of temperature distribution of a simply supported naked solid steel beam under fire exposure. Prescriptive based approach particularly is the safest and easiest approach to determine the level of strength of structural member when expose to elevated temperature. However, this method assuming uniform fire exposure through the overall cross section of the structural member which may leads to over design. The outcome of the design may not reflect the real fire scenario. Performance based approach is a realistic approach which can predict the structural steel behavior. In this method, three main components were considered, namely fire exposure behavior, heat transfer analysis and mechanical reaction. Fire exposure behavior dealing with types or severity fire load exposed to structural member. There are few options available to determine the fire extent, namely nominal fire models, compartment fires, localized fires, zone models and computational fluid dynamics (CFD) models. Meanwhile, heat transfer analysis estimates the energy dissipation (initiate from fire) between structural elements due to temperature variation. Structural response incorporates finite element modeling that predicts the structural element behavior, namely stresses and deformation. This method considers the prime factors such as shadow effect, support condition, loading condition, boundary conditions and interaction properties between different structural elements which can optimize the structural behavior analysis. However, there are still lack of research that consider those factors that might jeopardize the behavior of steel beam. Owing to this, a performance based approach method was introduced in this research. Experimental investigation was retrieved from the readily available data of Compendium of UK Standard Fire Test Data. One sample of naked solid steel beam was selected from the wide range of naked solid beam available from the Compendium. Standard fire curve of ISO 834 was used during numerical simulation to correlate with the experimental investigation. From the results of the finite element simulation, the predicted member temperature agrees well with the experimental investigations. Hence, future works of cellular steel beam (CSB) with various web opening shapes can be initiate due to its limited researches related to CSB at elevated temperatures